Fertiliser use and soil carbon sequestration: trade-offs and opportunities - Hijbeek, Renske; Loon, Marloes P. van; Ittersum, Martin K. van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Current initiatives to store carbon in soils as a measure to mitigate climate change are gaining momentum. Agriculture plays an important role in soil carbon initiatives, as almost 40% of the world’s soils are currently used as cropland and grassland. Thus, a major research and policy question is how different agricultural management practices affect soil carbon sequestration. This working paper focuses on the impact of mineral fertiliser use on soil carbon sequestration, including synergies with the use of organic inputs (for example crop residues, animal manure) and trade-offs with greenhouse gas (GHG) emissions. Findings from scientific literature show that fertiliser use contributes to soil carbon sequestration in agriculture by increasing biomass production and by improving carbon:nitrogen (C:N) ratios of residues returned to the field. The use of mineral fertiliser can also support the maintenance of carbon stocks in non-agricultural land if improved fertility on agricultural land reduces demand for land conversion. Combining organic inputs with mineral fertiliser seems most promising to sequester carbon in agricultural soils. Increasing nutrient inputs (either organic or mineral fertilisers) may however lead to trade-offs with GHG emissions such as N2O. Improving the agronomic nitrogen use efficiency of nutrient inputs (i.e., additional grain yield per kg N applied) can alleviate this trade-off. While soil carbon sequestration can benefit soil fertility under some conditions and compensate for some GHG emissions related to agriculture (first assessments indicate up to 25% of the emissions related to crop production, depending on region and cropping system), it seems unlikely it can compensate for GHG emissions from other economic sectors. If soil carbon sequestration is a policy objective, priorities should be areas with higher storage potential (wetter and colder climates) and/or regions where synergies with soil fertility and food security are likely to occur (for example farming systems in tropical regions, on sandy soils and/or when cultivating more specialized crops). However, regions with the highest storage potential most likely do not overlap with regions where the largest benefits for soil fertility and food security occur.